DETERMINAN KUALITAS AUDIT STUDI EMPIRIS PADA INSPEKTORAT PEMERINTAH PROVINSI BANTEN - Qodriyat, Yodi Ero; Yazid, Helmi (JURNAL RISET AKUNTANSI TIRTAYASA, 2018)
This study aims to examine the determinants of audit quality in Inspectorate of Banten Province. This research develops theoretical framework as the basis of hypothesis, to answer the research questions consisting of: (1) Does the auditor's performance have an effect on audit quality, (2) Does management support affect audit quality, (3) Does computer-based audit technique influence (6) Does the work environment affect the quality of the audit, (7) Does the availability of budgets affect the quality of the audit, (4) Does the quality of the audit work, and (8) Does the auditor's professional ethics affect the quality of the audit. The sample of this study was 71 people auditor Inspectorate ofBanten Province. Data are primary data collected through questionnaires. Data analysis method to test the hypothesis is Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS). The results of this study indicate that the auditor's performance, training and development, as well as the ethics of the auditor profession have a positive effect on audit quality, while for managementsupport, computer-assisted audit techniques, promotion and rewards, work environment and budget availability have no positive effect on audit quality. Keywords : Auditor Performance, Management Support, Audit Engineering, Training and Development, Promotion and Awards, Work Environment, Budget Availability and Audit Quality.